Penyuluhan Pertanian Pada Era Kenormalan Baru di Kota Denpasar - WINDIARI, ANAK AGUNG AYU NGURAH RIKA; SUARDI, I DEWA PUTU OKA; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022DO - 10.24843/JAA.2022.v11.i02.p31, 2022)
Agricultural Extension during New Normal Era in Denpasar The study aimed at (1) the implementation of agricultural extension activities during the New Normal Era (2) the challenges faced by the agricultural extensionists (3) the efforts to solve the problems. The poor implementation includes the preparation, online monitoring, and evaluative reports caused by the uncertain conditions. The obstacles faced in administration, technical infrastructure, supporting facilities, farmer participation, and the IT skill of extensionists. A less good condition of solution was found yet identified as good enough for farmer participation. The data used are primary and secondary data, the methods implemented are questionnaires and interviews. The qualitative and quantitative were data analysis. The results of the study: (1) characteristics of Agricultural Extensionists in Denpasar, 16 persons, average age 53 years 38%, Bachelor 94%, balanced men and women, 50% is civil servant 63%, work experience on average 11 years 50%, the family dependents 48% on average. The characteristics of Subak Head, 12 people: average age 52 years 25%, junior high school graduated 33%,100% male, work experience on average 3 years 50%.(2) the implementation of agricultural extensionists in Denpasar according to PPL is classified as poor category, 56% of respondents. Subak Head counseling was carried out offline, by mobile phone, and by zoom meeting, it was not good, 67% respondents, the material was quite good, 75% respondents. (3) obstacles based on the research results are classified as poor, 56% respondents. (4) efforts to overcome obstacles to agricultural extensionists in the New Normal Era in Denpasar, 69% respondents were not good.